An Optimized 3D Coculture Assay for Preclinical Testing of Pro- and Antiangiogenic Drugs. (June 2017) - Unterleuthner, Daniela; Kramer, Nina; Pudelko, Karoline; Burian, Alexandra; Hengstschläger, Markus; Dolznig, Helmut
Angiogenesis is a promising target for anticancer therapies, but also for treating other diseases with pathologic vessel development. Targeting the vascular endothelial growth factor (VEGF) pathway did not proof as effective as expected due to emerging intrinsic resistance mechanisms, as well as stromal contributions leading to drug insensitivity. Therefore, alternative strategies affecting the interaction of endothelial cells (ECs) with other stromal cells seem to be more promising. Human preclinical in vitro angiogenesis models successfully recapitulating these interactions are rare, and two-dimensional (2D) cell cultures cannot mimic tissue architecture in vivo. Consequently, models combining three-dimensionality with heterotypic cell interaction seem to be better suited. Here, we report on an improved human fibroblast–EC coculture assay mimicking sprouting angiogenesis from EC-covered microbeads resembling existing endothelial structures. Culture conditions were optimized to assess pro- and antiangiogenic compounds. Important characteristics of angiogenesis, that is, the number of sprouts and branch points, sprout length protrusion, and overall vessel structure areas, were quantified. Notably, the endothelial sprouts display lumen formation and basal membrane establishment. In this model, angiogenesis can be inhibited by genetic interference of pro-angiogenic factors expressed in the fibroblasts. Moreover, bona fide antiangiogenic drugs decreased, whereas pro-angiogenic factors increased vessel formation in 24-well and 96-well settings, demonstrating the applicability for screening approaches.